At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
implifying cos(x) = -1cos(y) Multiply cos * x cosx = -1cos(y) Multiply cos * y cosx = -1cosy Solving cosx = -1cosy Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add 'cosy' to each side of the equation. cosx + cosy = -1cosy + cosy Combine like terms: -1cosy + cosy = 0 cosx + cosy = 0 Factor out the Greatest Common Factor (GCF), 'cos'. cos(x + y) = 0 Subproblem 1 Set the factor 'cos' equal to zero and attempt to solve: Simplifying cos = 0 Solving cos = 0 Move all terms containing c to the left, all other terms to the right. Simplifying cos = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. Subproblem 2 Set the factor '(x + y)' equal to zero and attempt to solve: Simplifying x + y = 0 Solving x + y = 0 Move all terms containing c to the left, all other terms to the right. Add '-1x' to each side of the equation. x + -1x + y = 0 + -1x Combine like terms: x + -1x = 0 0 + y = 0 + -1x y = 0 + -1x Remove the zero: y = -1x Add '-1y' to each side of the equation. y + -1y = -1x + -1y Combine like terms: y + -1y = 0 0 = -1x + -1y Simplifying 0 = -1x + -1y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
@MasterGeen no copy and paste please
YOU WANTED AN ANSWER RIGHT LOL
cos(x)=cos(y)-->x=2kpi+y and x=2kpi-y
@amirreza1870 how did you get that?
Cos and Sin have period of 2pi, i.e. cos(x+2pi)=cos(x) for exemple. WIth that in mind, cos(x) = cos(y) then \(x = y+2n\pi, n\in N\)
@M4thM1nd what about the other solution?
the period of cos(x) is 2pi for example cos60=cos420 so the first answer was 2kpi+y then you know that cos(-x)=cos(x) so the second answer is 2kpi-y.
another solution is due the fact that Cos is an even function, i.e. cos(-x) = cos(x). So... \(x = -y+2n\pi, n\in N\)
Ok, make sense. But isn't it more like "insight" than actual computation?
m4th mind helping me after?
For a more step-by-step solution, cos(x) = cos(y) x = acos(cos(y)) \(x=\pm y+2n\pi\)
but inverse cosine can only gives a value between [0,pi]
I missed the solution -x = y + (2pi)n initially because didn't realize cos(-x) = cos(x).
yes, the range of acos(x) is [0, pi], but you get to keep in mind that cos is positive in the first and fourth quadrant and negative in second and third. So, if you evaluate acos(cos(3pi/2)) you will get 3pi/4 for example. This means we have a "refletion" around x = pi, for possible solutions
Ok. Makes sense. Thank you